Clinical safety and efficacy of allogenic human adipose mesenchymal stromal cells-derived exosomes in patients with mild to moderate Alzheimer’s disease: a phase I/II clinical trial - Xie, Xinyi; Song, Qingxiang; Dai, Chengxiang; Cui, Shishuang; Tang, Ran; Li, Suke; Chang, Jing; Li, Ping; Wang, Jintao; Li, Jianping; Gao, Chao; Chen, Hongzhuan; et al. (General psychiatry, 2023)
BackgroundThere have been no effective treatments for slowing or reversing Alzheimer’s disease (AD) until now. Growing preclinical evidence, including this study, suggests that mesenchymal stem cells-secreted exosomes (MSCs-Exos) have the potential to cure AD.AimsThe first three-arm, drug-intervention, phase I/II clinical trial was conducted to explore the safety and efficacy of allogenic human adipose MSCs-Exos (ahaMSCs-Exos) in patients with mild to moderate AD.MethodsThe eligible subjects were assigned to one of three dosage groups, intranasally administrated with ahaMSCs-Exos two times per week for 12 weeks, and underwent follow-up visits at weeks 16, 24, 36 and 48.ResultsNo adverse events were reported. In the medium-dose arm, Alzheimer’s Disease Assessment Scale–Cognitive section (ADAS-cog) scores decreased by 2.33 (1.19) and the basic version of Montreal Cognitive Assessment scores increased by 2.38 (0.58) at week 12 compared with baseline levels, indicating improved cognitive function. Moreover, the ADAS-cog scores in the medium-dose arm decreased continuously by 3.98 points until week 36. There were no significant differences in altered amyloid or tau deposition among the three arms, but hippocampal volume shrank less in the medium-dose arm to some extent.ConclusionsIntranasal administration of ahaMSCs-Exos was safe and well tolerated, and a dose of at least 4×108 particles could be selected for further clinical trials.Trial registration number NCT04388982.